2015
DOI: 10.1007/s11524-015-0008-7
|View full text |Cite|
|
Sign up to set email alerts
|

Who Shot Ya? How Emergency Departments Can Collect Reliable Police Shooting Data

Abstract: This paper examines an alternative solution for collecting reliable police shooting data. One alternative is the collection of police shooting data from hospital trauma units, specifically hospital-based violence intervention programs. These programs are situated in Level I trauma units in many major cities in USA. While the intent of these programs is to reduce the risk factors associated with trauma recidivism among victims of violent injury, they also collect reliable data on the number of individuals treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…4,5 Others have explored various options for using public health monitoring systems to provide better data to epidemiologists and the public on police-related fatalities and gunshot injuries. [6][7][8] Still, others have produced analyses of existing injury and mortality data derived from hospital records and death certificates. [9][10][11] Researchers have yet to answer basic epidemiological questions about police violence, however, such as whether the incidence rate of injuries caused by US police has changed over time, or the degree to which these injuries are properly coded as Blegal intervention^(i.e., those caused by law enforcement, as per the International Classification of Diseases (ICD)) and are therefore identifiable in statistical analyses of hospital data.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Others have explored various options for using public health monitoring systems to provide better data to epidemiologists and the public on police-related fatalities and gunshot injuries. [6][7][8] Still, others have produced analyses of existing injury and mortality data derived from hospital records and death certificates. [9][10][11] Researchers have yet to answer basic epidemiological questions about police violence, however, such as whether the incidence rate of injuries caused by US police has changed over time, or the degree to which these injuries are properly coded as Blegal intervention^(i.e., those caused by law enforcement, as per the International Classification of Diseases (ICD)) and are therefore identifiable in statistical analyses of hospital data.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of gun violence in particular have utilized such data (e.g., D. J. Boyle et al, 2010; Richardson et al, 2016), given that gunshot wound victims may seek medical attention but want to avoid contact with the police. These analyses similarly find that hospital data uncover more violence than relying on police data alone.…”
Section: Prior Researchmentioning
confidence: 99%
“…Opinions in the nation’s largest newspapers lament the lack of solid, government-collected data covering police killings of civilians (Berman, 2015; Lowery, 2014). A former FBI Director described federal data on justifiable killings as unreliable due to voluntary reporting requirements, describing journalists instead as the “lead sources” in determining the scope of the problem (Tran, 2015) and a former Attorney General made similar comments (Richardson et al, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The undercounting of civilian homicide (Maltz, 2006) compounds when we shift to police homicide, shifting the vectors of concern as well. Richardson et al (2015) report that in 2012 only 4% of jurisdictions (about 750 of 18,000) reported police killings to the FBI. Directly contrary to civilian homicides, this extreme undercounting stemmed in part from “large jurisdictions that do not routinely report police-involved deaths” including one jurisdiction of more than 1300 officers which “did not view justifiable homicides by law enforcement officers as reportable data”.…”
Section: Theoretical Backgroundmentioning
confidence: 99%